2011
DOI: 10.1002/ejsp.795
|View full text |Cite
|
Sign up to set email alerts
|

Grounding person memory in space: Does spatial anchoring of behaviors improve recall?

Abstract: In two experiments, we examine and find support for the general hypothesis that memory for behavioral information in the context of an impression formation task depends on where that information is located in vertical space. These findings extend earlier work showing that memory for location and shifts of spatial attention are influenced by the ''good is up'' metaphor. Specifically, we show that person memory is better for behavioral information in metaphor compatible locations (positive in upper space and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
2
14
1
1
Order By: Relevance
“…In the domain of attention, Moeller et al ( 2008 ) showed that when individuals were presented with a metaphor “good is up/bad is down,” individual differences in perceived social power had an impact on spatial attention in a metaphor-consistent manner. In the domain of memory, Crawford et al ( 2006 ) showed that individuals remember the metaphor “good is up” better when it is presented in a higher position (see also Palma et al, 2011 ). In the domain of attitudes, researchers showed that political attitudes can be understood in terms of a horizontal spatial axis (Oppenheimer and Trail, 2010 ; Farias et al, 2013 ), morality in terms of cleanliness (Schnall et al, 2008 ), good and moral in terms of bright color, and bad and immoral in terms of black color (Meier et al, 2007 ; Sherman and Clore, 2009 ).…”
Section: Embodied Theory and Researchmentioning
confidence: 99%
“…In the domain of attention, Moeller et al ( 2008 ) showed that when individuals were presented with a metaphor “good is up/bad is down,” individual differences in perceived social power had an impact on spatial attention in a metaphor-consistent manner. In the domain of memory, Crawford et al ( 2006 ) showed that individuals remember the metaphor “good is up” better when it is presented in a higher position (see also Palma et al, 2011 ). In the domain of attitudes, researchers showed that political attitudes can be understood in terms of a horizontal spatial axis (Oppenheimer and Trail, 2010 ; Farias et al, 2013 ), morality in terms of cleanliness (Schnall et al, 2008 ), good and moral in terms of bright color, and bad and immoral in terms of black color (Meier et al, 2007 ; Sherman and Clore, 2009 ).…”
Section: Embodied Theory and Researchmentioning
confidence: 99%
“…Consistent with this, Andrade and Donaldson (2007) found reduced odor recognition memory with a concurrent odor task during encoding compared to a concurrent verbal or visual task. Alternatively, memory performance could be improved because the overlap may increase overall activation, thereby strengthening the memory trace (as in Engelkamp, 2001;Palma, Garrido, & Semin, 2011;Parzuchowski & Szymkow-Sudziarska, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research to date has documented that abstract concepts like "affect", "power" or "time" implicitly activate spatial associations (e.g., Boroditsky, 2000;Crawford, Margolies, Drake, & Murphy, 2006;Körner, Topolinski, & Strack, 2015;Lakens, Semin, & Garrido, 2011;Meier & Robinson, 2004;Palma, Garrido, & Semin, 2011;Schubert, 2005). More recently, others have shown that the political categories of left and right are represented horizontally in space (e.g., van Elk, van Schie, & Bekkering, 2010;Farias, Garrido, & Semin, 2013;Garrido, Farias, & Semin, 2015;Oppenheimer & Trail, 2010).…”
Section: Introductionmentioning
confidence: 99%